Quantification and Prediction of Imine Formation Kinetics in Aqueous Solution by Microfluidic NMR Spectroscopy. Issue 37 (27th May 2021) - Zhuo, Youzhen; Wang, Xiuxiu; Chen, Si; Chen, Hang; Ouyang, Jie; Yang, Liulin; Wang, Xinchang; You, Lei; Utz, Marcel; Tian, Zhongqun; Cao, Xiaoyu
Abstract: Quantitatively predicting the reactivity of dynamic covalent reaction is essential to understand and rationally design complex structures and reaction networks. Herein, the reactivity of aldehydes and amines in various rapid imine formation in aqueous solution by microfluidic NMR spectroscopy was quantified. Investigation of reaction kinetics allowed to quantify the forward rate constants k + by an empirical equation, of which three independent parameters were introduced as reactivity parameters of aldehydes ( SE, E ) and amines ( N ). Furthermore, these reactivity parameters were successfully used to predict the unknown forward rate constants of imine formation. Finally, two competitive reaction networks were rationally designed based on the proposed reactivity parameters. Our work has demonstrated the capability of microfluidic NMR spectroscopy in quantifying the kinetics of label‐free chemical reactions, especially rapid reactions that are complete in minutes. Abstract : The imine formation in aqueous solution that was finished within several minutes by microfluidic NMR spectroscopy was investigated. The forward rate constants k + were quantified by an empirical equation containing three independent parameters: reactivity parameters of aldehydes ( SE, E ) and amines ( N ). These results allow the prediction of the unknown forward rate constant k + and rational design of two reaction networks exhibiting kinetic selectivity.